Injection drug use practices and HIV infection among people who inject drugs in Kigali, Rwanda: a cross-sectional study - Jean Olivier Twahirwa Rwema; Vianney Nizeyimana; Neia M. Prata; Nneoma E. Okonkwo; Amelia A. Mazzei; Sulemani Muhirwa; Athanase Rukundo; Lisa Lucas; Audace Niyigena; Jean Damascene Makuza; Chris Beyrer; Stefan D. Baral; et al. (BMC, 2021)
Abstract Background In Rwanda, epidemiological data characterizing people who inject drugs (PWID) and their burden of HIV are limited. We examined injection drug use (IDU) history and practices, and HIV infection in a sample of PWID in Kigali. Methods From October 2019 to February 2020, 307 PWID aged ≥ 18 were enrolled in a cross-sectional study using convenience sampling in Kigali. Participants completed interviewer-administered questionnaires on IDU history and practices and HIV testing. We used Poisson regression with robust variance estimation to assess IDU practices associated with HIV infection and assessed factors associated with needle sharing in the six months preceding the study. Results The median age was 28 years (IQR 24-31); 81% (251) were males. Female PWID were more likely to report recent IDU initiation, selling sex for drugs, and to have been injected by a sex partner (p < 0.05). In the prior six months, heroin was the primary drug of choice for 99% (303) of participants, with cocaine and methamphetamine also reported by 10% (31/307) and 4% (12/307), respectively. In total, 91% (280/307) of participants reported ever sharing needles in their lifetime and 43% (133) knew someone who died from a drug-related overdose. HIV prevalence was 9.5% (95% CI 8.7-9.3). Sharing needles at least half of the time in the previous six months was positively associated with HIV infection (adjusted prevalence ratio (aPR) 2.67; 95% CI 1.23-5.78). Overall, 31% (94/307) shared needles and 33% (103/307) reused needles in the prior six months. Female PWID were more likely to share needles compared to males (aPR 1.68; 95% CI 1.09-2.59). Additionally, bisexual PWID (aPR 1.68; 95% CI 1.09-2.59), those who shared needles at the first injection (aPR 2.18; 95% CI 1.59-2.99), reused needles recently (aPR 2.27; 95% CI 1.51-3.43) and shared other drug paraphernalia (aPR 3.56; 95% CI 2.19-5.81) were more likely to report recent needle sharing. Conclusion HIV infection was common in this study. The high prevalence of needle reuse and sharing practices highlights significant risks for onward transmission and acquisition of HIV and viral hepatitis. These data highlight the urgent need for PWID-focused harm reduction services in Rwanda, including syringe services programs, safe injection education, naloxone distribution, and substance use disorder treatment programs and optimizing these services to the varied needs of people who use drugs in Rwanda.